Evaluasi Proses Manajemen Asset dan Manajemen Layanan Keamanan Internal pada PT Amman Mineral Nusa Tenggara menggunakan Framework Cobit 5 - Ade Listiawan; Admaja Dwi Herlambang; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
PT Amman Mineral Nusa Tenggara has used information technology to support its business processes. Governance contains a structure of policies and procedures and a collection of IT processes to achieve institutional goals. In this study using a qualitative non-implementative method by collecting observation, interview and questionnaire data in accordance with the COBIT 5 framework. The main problem that is often encountered is that many assets are unused, damaged and even lost. In addition, in terms of service security, there are also problems with the process of data management where improper access rights, and outgoing data are not monitored properly resulting in information or data leakage. The focus of this research is on the process of asset management, security services, especially in the IT department, assessing the level of capability and gap analysis that exists in the IT department at PT Amman Mineral Nusa Tenggara. Capability level is a process capability in achieving a capability level in a company that has been determined by certain process attributes and criteria. The capability level obtained at the department in the BAI09 - Manage Asset process is Level 3 - Established Process as much as 97.22% and DSS05 - Manage Security Services is Level 4 - Predictable Process as much as 96.42%. The target level in the IT department is Level 5 so that the gap found in BAI09 is two levels, while DSS05 is one level.